Integration of Heterogeneous Databases and Ontologies - Oscar Luiz Monteiro de Farias, Neide dos Santos, Adriana dos Santos Aparício (Cadernos do IME - Série Informática, 2013)
Research in interoperability has been motivated by the growing heterogeneity of computing systems. Heterogeneity can occur in many levels and each level of heterogeneity requires an isolated or integrated approach for solution. In this paper, we propose the specification of a formal ontology for the information related to a specific domain of a database system, to work together with a global scheme, developed as software layer among the different databases under consideration. To test this approach we elaborated a case study, based upon hypothetical queries submitted to relational and heterogeneous databases, with data on soil domain, aiming at identifying the kinds of soil most appropriate to a certain culture. The case study demonstrated that the semantic conflicts were circumvented and the integration of the databases was easily reached.